A Gazetteer of Buildings in Muslim Palestine - Petersen, Andrew (Council for British Research in the Levant, 2001)
The aim of the survey on which this book is based was to make a record of all buildings constructed in Palestine during the medieval and Ottoman periods. The survey area covers the modern state of Israel excluding West Jerusalem and Ramla (which are covered in separate publications). The West Bank and Gaza will be the subject of Volume II. Library of Congress subject headings for this publication: Architecture, Islamic -- Palestine -- Guidebooks. Architecture, Ottoman -- Palestine -- Guidebooks. Architecture, Medieval -- Palestine -- Guidebooks. Historic buildings -- Palestine -- Guidebooks.